The Association Between Connectedness and Grit Among Thai In-school Adolescents in Urban Chiang Mai, Thailand - Tangmunkongvorakul, Arunrat; Kelly, Matthew; Thongpibul, Kulvadee; Musumari, Patou Masika; Srithanaviboonchai, Kriengkrai; Banwell, Cathy (Frontiers in Psychology, 2022)
Aim: To investigate the associations between Grit, connectedness, and parental involvement in Thai adolescents. Grit, perseverance and passion for long term goals are predictors of academic success and health. There is a small but developing knowledge of the predictors of grit in Asia, especially Thailand. This paper investigates the proposition that connectedness and parental involvement are positively associated with Grit. Method: A total of 2,839 lower secondary (grade 8), higher secondary (grade 11), and vocational (year 12) students from 21 schools in Chiang Mai, Thailand participated in a survey that measured Grit using the Short Grit Scale. Bivariate analysis was conducted using the t-test, ANOVA, or Kruskal-Wallis H test as appropriate. Multiple ordinary least squares linear regression analysis was performed to determine factors associated with Grit. Results: Satisfactory relationships with teachers (P=0.01), parental support (P=0.03), interest in school (P=0.01), having been asked by parents to do homework ( = -0.69; P= 0.012), and having been told by parents that they had done something bad ( = -1.09; P=0.02) associated with Grit. These findings can aid in design of tailored interventions to improve Grit in Thai adolescents.